Severe Sinus Bradycardia in Puumala virus infection. (February 2019) - Pastissier, Andréa; Humbert, Sébastien; Naudion, Pauline; Meaux-Ruault, Nadine; Badoz, Marc; Magy-Bertrand, Nadine
Highlights: Puumala virus is the most prevalent of the four types of hantaviruses found in Europe. Puumala virus is responsible for nephropathia endemic, a mild form of hemorrhagic fever with renal syndrome. A severe bradycardia can occur during a Puumala virus infection. Abstract: Puumala orthohantavirus (PUUV) is the most prevalent of the four species of zoonotic hantaviruses found in Europe, causing nephropathia epidemica, a mild form of hemorrhagic fever with acute kidney injury that presents with elevated serum creatinine level, proteinuria and hematuria. The febrile phase of the infection begins with flu-like syndrome and visual disturbance. Laboratory results can show thrombocytopenia. The oliguric phase with elevated serum creatinine level then occurs. Cardiac involvement is sometimes observed, especially ECG abnormality: transient T-waves inversion, generally in the lateral or inferior leads. Marked bradycardia has been exceptionally described. We report the case of a 36-year-old woman with acute PUUV infection. Two days after admission, the patient presented a sinus bradycardia at 25/min. The bradycardia was asymptomatic, persisted one week and resolved spontaneously. Cardiac involvement in Puumala virus infection seems not to be associated with a bad prognosis. Bradycardia in the course of an influenza-like illness in endemic areas should suggest several pathogens such as legionella, Q fever or PUUV virus infection.